Playing the takeover market : how to profit from corporate mergers, spinoffs, tender offers, and liquidations - McQuown, Judith H. (New York : Seaview books, 1982)
The book provides solid strategies for investing in takeover stocks. By applying methods used by professionals for years, MCQuown shows how any investor can identify companies that are ripe for takeover by using commonsense deduction, by picking up signals in the press, by charting trends, and by analyzing a few key elements of a company's balance sheet. She examined the pros and cons of buying a stock before a tender offer has been made.
Includes index.
Bibliography: p. [241]
rua 27/02/2017
Loans
Keywords: Mergers ans acquisitions; Consolidation and merger of corporations; Corporate reorganizations